O espelho do colonialismo : imaginário e representações na 1.ª Exposição Colonial Portuguesa (1934) - Mesquita, Karla Ribeiro Gabriel (2022)
The present dissertation: The mirror of colonialism: Imaginary and Representations in the 1st Portuguese Colonial Exhibition (1934), aims to investigate the representation of the female gender in the 1st Portuguese Colonial Exhibition (1934). The photographs produced in this event are the sources of this work, as well as written documents and images of another nature, such as illustrations, caricatures and cartoons. Based on the bibliographic review and analysis of the sources, we tried to establish relationships between the Exhibition, colonialism and the Portuguese imaginary. Some theorists are fundamental in this study, such as the historian Boris Kossoy and the philosopher Gilbert Durand. The trajectory of the photographers is also fundamental in this investigation, as well as the director of the Exhibition and the socio-political context in which the event took place. Thus, we intend to present three chapters that discuss the issues already mentioned.